PERSEPSI PETANI TENTANG INOVASI PENGELOLAAN TANAMAN TERPADU (PTT) - Kusmiyati Kusmiyati; Dedy Kusnadi (Politeknik Pembangunan Pertanian Bogor, 2020)
The adoption of innovation is affected by perception of farmers. The aims of this research are: (1) to explain the farmers internal factors and its correlations with innovations perception; (2) to explain the farmers external factors and its correlations with innovation’s perception; and (3) to explain the level of farmers' perceptions about innovation. This research was conducted from June until September 2010 in Dramaga District, Bogor regency, West Java Province. The results showed internal and external factors are correlated to farmer perceptions. The farmers’ age, and formal education and availability of market are real correlated with farmers innovations perception (rs=0.323; 0.374; and -0.395; respectively). The average level of farmers inovation perceptions is 84% moderate up to very high.